Keadilan Substantif Dalam Perkara Cybercrime: Studi Perbandingan Putusan Baiq Nuril (Indonesia) Dan United States V. Aleynikov (As) - Muhammad Rizky Syafrizal; Frayoga Agustian; Habib Nurhammad; Riandra mahanugrah; Tegar Septian Gumilang; Asep Suherman (CV. ITTC INDONESIA, 2026)
This study aims to analyze the application of substantive justice in cybercrime cases through a comparative study of the Supreme Court Decision of the Republic of Indonesia No. 574 K/Pid.Sus/2018 in the Baiq Nuril case and the United States v. Aleynikov case (No. 12-2075, 2nd Cir. 2012). This research employs a normative legal method with statutory, case, conceptual, and comparative approaches. The findings indicate that in the Baiq Nuril case, the court emphasized a formal-legalistic approach, which did not fully reflect substantive justice. In contrast, in United States v. Aleynikov, the court strictly applied the principle of legality, prioritizing legal certainty over substantive justice considerations. The differences between the civil law system in Indonesia and the common law system in the United States influence judicial reasoning in cybercrime adjudication. This study concludes that a balance between legal certainty and substantive justice is required in cybercrime enforcement to ensure a responsive legal system in the digital era.